WATAK HARMONIK PADA INVERTER TIGA FASA TAK BERBEBAN - Sunanda, Wahri; Rahman, Yuli Asmi (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2011)
AbstractHarmonic is one of sinusoidal components, one wave period from whichhaving multiple frequency of its fundamental frequency one, leading toelectrical power quality problems. Harmonic distortion in term of voltageand current ones, generally is due to non linier impedance. Inverter is one ofexample of it. There are some items that will be measured. There are value ofharmonic at source and value of voltage and current harmonic when inverter does not have any load. IEEE Standard of 5191992 as a reference in determining maximum limitation voltage and current harmonics. The result of the tests were showed that voltage harmonic distortion at inverter did not exceed the IEEE 5191992 maximum limitation of 5%. While current harmonic distortion had exceed the maximum limitation of the IEEE 5191992. The highest results were exceeding 56,55 % when inverter does not have any load.Keywords: Voltage, Current, Harmonic Distortion, Inverter.